On the nature of superconductivity in the anisotropic dichalcogenide NbSe2CoCp2x. (27th March 2015) - Scheidt, E-W; Herzinger, M; Fischer, A; Schmitz, D; Reiners, J; Mayr, F; Loder, F; Baenitz, M; Scherer, W
Abstract: We present a detailed study of the superconducting properties of the weakly pinned, quasi-two-dimensional superconductor 2H-NbSe2, and its intercalated variant NbSe2 {CoCp2 }0.26 . The intercalation of 2H-NbSe2 with the organometallic donor molecule cobaltocene (CoCp2 ) hardly affects the superconducting properties within the layers. However, the properties perpendicular to the layers change significantly due to the large expansion of the layer spacings of the host lattice in the c -direction by a factor of about two. In particular, the superconducting anisotropy factor Γ increases from 3.3 in the parent compound 2H-NbSe2 up to 4.4 in the intercalated species. Therefore, NbSe2 {CoCp2 }0.26 is an excellent candidate to analyze how the anisotropy effects the superconducting mechanism in layered dichalcogenides, and to evaluate the various models proposed in the literature to account for the anisotropy in 2H-NbSe2 . While a two-gap model and an anisotropic single-gap model are competing concepts to describe the almost linear T 2 -dependence of Δ C / T in low-dimensional dichalcogenides, our comparative study suggests that a single-gap model with an anisotropic Fermi-surface is sufficient to capture the Δ C / T ( T ) behavior in our samples qualitatively.